A systematic scoping review of the methodological approaches and effects of pesticide exposure on solitary bees. - David M Lehmann; Allison A Camp (PLoS ONE)
Background Pollination services provided by solitary bees, the largest group of bees worldwide, are critical to the vitality of ecosystems and agricultural systems alike. Disconcertingly, bee populations are in decline, and while no single causative factor has been identified, pesticides are believed to play a role in downward population trends. The effects of pesticides on solitary bee species have not been previously systematically cataloged and reviewed. Objectives This systematic scoping review examines available evidence for effects of pesticide exposure on solitary bees to identify data gaps and priority research needs. Methods A systematic literature search strategy was developed to identify and document reports on solitary bee pesticide exposure-effects investigations. Literature was subsequently screened for relevance using a Population, Exposures, Comparators, and Outcomes (PECO) statement and organized into a systematic evidence map. Investigations were organized by effect category (lethal effects on immatures, lethal effects on adults, sublethal effects on immatures, and sublethal effects on adults), species, pesticide class, and publication year. Results A comprehensive literature search of Web of Science and ProQuest Agricultural & Environmental Science supplemented by targeted internet searching and reference mining yielded 176 reports and publications for title and abstract screening and 65 that met PECO criteria (22 included lethal and 43 included sublethal effects endpoints). Relevant design details (pesticide, test compound configuration, study type, species, sex, exposure duration) were extracted into literature inventory tables to reveal the extent endpoints have been investigated and areas in need of additional research. Conclusions Evidence mapping revealed diversity in the pesticides and endpoints studied across the database. However, dilution across bee species, lack of complementary laboratory work and paucity of replicated investigations complicate efforts to interpret and apply available data to support pesticide risk assessment.